2023
DOI: 10.3390/biomedicines11051356
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin as a Biomarker in Chronic Kidney Disease

Abstract: Osteopontin (OPN) is a ubiquitously expressed protein with a wide range of physiological functions, including roles in bone mineralization, immune regulation, and wound healing. OPN has been implicated in the pathogenesis of several forms of chronic kidney disease (CKD) where it promotes inflammation and fibrosis and regulates calcium and phosphate metabolism. OPN expression is increased in the kidneys, blood, and urine of patients with CKD, particularly in those with diabetic kidney disease and glomerulonephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 137 publications
(191 reference statements)
1
7
0
Order By: Relevance
“…Of note, the renal risk score with COIA1 included was able to predict rapid renal decline in a small subset of patients with longitudinal measures, as defined in Xu et al, 9 indicating its prognostic value as well (N = 67, OR = 1.475, p = 0.0343). Many other proteins associated with eGFR < 60 in this study have been previously proposed as biomarkers for various types of kidney disease including osteopontin (OSTP), 75 pancreatic ribonuclease (RNAS1), 76 prostaglandin-H2 D-isomerase (PTGDS), 77 and β-2-microglobulin (B2MG), 78 among others, providing additional confidence in our results. Moreover, pathway analysis identified an enrichment of ECM, cell adhesion, and BM proteins, all of which are essential not only for structural integrity of the kidney but also for signaling, growth, differentiation, and function.…”
Section: ■ Discussionsupporting
confidence: 76%
“…Of note, the renal risk score with COIA1 included was able to predict rapid renal decline in a small subset of patients with longitudinal measures, as defined in Xu et al, 9 indicating its prognostic value as well (N = 67, OR = 1.475, p = 0.0343). Many other proteins associated with eGFR < 60 in this study have been previously proposed as biomarkers for various types of kidney disease including osteopontin (OSTP), 75 pancreatic ribonuclease (RNAS1), 76 prostaglandin-H2 D-isomerase (PTGDS), 77 and β-2-microglobulin (B2MG), 78 among others, providing additional confidence in our results. Moreover, pathway analysis identified an enrichment of ECM, cell adhesion, and BM proteins, all of which are essential not only for structural integrity of the kidney but also for signaling, growth, differentiation, and function.…”
Section: ■ Discussionsupporting
confidence: 76%
“…During kidney injury, its presence is significantly increased in all tubular segments and especially in the glomeruli [268]. The role of OPN in DKD has been reviewed in detail by our group recently [269]. During the last decade, a number of studies analyzed the role of OPN in the pathogenesis of DKD and reported high expression of OPN in the tubular epithelium of the renal cortex and in glomeruli in rat and mouse models of DKD [270,271].…”
Section: Opn-mediated Fibrosis In Dkdmentioning
confidence: 99%
“…A plethora of clinical trials have investigated the relationship of OPN with the presence, severity and prognosis of ASCVDs like CAD and PAD. Although several OPN inhibitors have been tested in cancer and chronic kidney disease, there are no clinical data assessing OPN modifiers (inhibitors or activators) in ASCVDs [41][42][43]. On the other hand, the existing data implicate that specific medications already prescribed in patients with ASCVDs, like statins, may influence the blood levels of OPN.…”
Section: Clinical Trials: the Relationship Between Opn And Ascvdsmentioning
confidence: 99%